Discussion. Issue 3 (3rd July 2019) - Singleton, David
ABSTRACT: This concluding commentary points to and examines elements and issues treated in the contributions to this collection – based on studies conducted in a number of countries and institutions – that have very wide relevance to language learning and teaching in higher education. This relevance is especially acute where learning and/or teaching is proceeding in languages which vary in their relationships with the learners and teachers in question. Thus, for example, the dichotomies of home/expatriate and native/non-native teachers are discussed, the various impacts (positive and negative) of teaching via an L2, and the mixed results associated with trilingual classes. What clearly emerges is a pressing need for all of the situations described in these pages to be researched further and more fully.